2018
DOI: 10.1007/s00394-018-1764-4
|View full text |Cite
|
Sign up to set email alerts
|

Diet as a moderator in the association of sedentary behaviors with inflammatory biomarkers among adolescents in the HELENA study

Abstract: A higher adherence to the Mediterranean diet or an antioxidant-rich diet may attenuate the onset of oxidative stress signs associated by sedentary behaviors, whereas a poor diet seems to increase inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…A cross-sectional study on 483 subjects, 7-15 years of age and of both sexes [85], demonstrated that high serum Hcy levels were associated not only with age ≥12 years (prevalence ratio (PR) = 2.56; p < 0.01), being male (PR = 3.74; p < 0.01), high blood pressure (PR = 1.97; p < 0.01), low HDL-c levels (PR = 1.21; p = 0.03), high triglyceride levels (PR = 1.62; p = 0.03), and being overweight (PR = 2.32; p = 0.02), but also with poor intake of foods (PR = 1.46; p = 0.02) that protect against HHcy, such as dark green vegetables, whole and enriched grain products, legumes, and citrus fruit. Arouca et al [86] found no positive correlation between high levels of Hcy and low adherence to the Mediterranean Diet or other "antioxidant diets" among adolescents in the Helena study.…”
Section: Children and Adolescentsmentioning
confidence: 81%
“…A cross-sectional study on 483 subjects, 7-15 years of age and of both sexes [85], demonstrated that high serum Hcy levels were associated not only with age ≥12 years (prevalence ratio (PR) = 2.56; p < 0.01), being male (PR = 3.74; p < 0.01), high blood pressure (PR = 1.97; p < 0.01), low HDL-c levels (PR = 1.21; p = 0.03), high triglyceride levels (PR = 1.62; p = 0.03), and being overweight (PR = 2.32; p = 0.02), but also with poor intake of foods (PR = 1.46; p = 0.02) that protect against HHcy, such as dark green vegetables, whole and enriched grain products, legumes, and citrus fruit. Arouca et al [86] found no positive correlation between high levels of Hcy and low adherence to the Mediterranean Diet or other "antioxidant diets" among adolescents in the Helena study.…”
Section: Children and Adolescentsmentioning
confidence: 81%
“…Our findings have plausible biologic mechanisms. Several dietary intervention studies have demonstrated significant changes in inflammatory markers, immune cell populations and response to oxidative stress with Mediterranean diet 8 45. Specifically, in Healthy Lifestyle in Europe by Nutrition in Adolescence study, adherence to a Mediterranean diet was associated with an attenuation in oxidative stress response in adolescents 45.…”
Section: Discussionmentioning
confidence: 99%
“…Several dietary intervention studies have demonstrated significant changes in inflammatory markers, immune cell populations and response to oxidative stress with Mediterranean diet 8 45. Specifically, in Healthy Lifestyle in Europe by Nutrition in Adolescence study, adherence to a Mediterranean diet was associated with an attenuation in oxidative stress response in adolescents 45. Similarly, in the randomised controlled trial of European Project on Nutrition in Elderly People, adherence to a Mediterranean diet for 1 year was associated with significant changes in innate and adaptive immunity as measured by T cell degranulation, cytokine production and co-receptor expression 8.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that consuming a properly composed diet has been associated with better health status, due to the protective effect against various chronic diseases [ 37 , 45 ]. Evidence regarding the role of diet quality on glucose and lipid metabolism and inflammatory markers has been established in multiple observational studies [ 45 , 46 , 47 , 48 , 49 ]. The authors reported that a plant-based pattern and the Mediterranean diet (characterized by a high consumption of vegetables, fruits, legumes, olive oil, and low consumption of red meats) are associated with favorable health status and less inflammation [ 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%